Hubungan antara Dukungan Sosial Keluarga dengan Penerimaan Diri Pada Santri Pondok Pesantren - Zulmi wahyuningsih; Mujidin; Yuzarion (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The purpose of this study was to determine the relationship between family social support and self-acceptance in Islamic boarding school students. This research is a quantitative study with a cluster random sampling technique, with a total of 112 subjects who attend Islamic boarding schools in Tidore archipelago. Data collection in this study used a self-acceptance scale and a family social support scale. The analytical method used is a statistical method with product moment analysis techniques based on the IBM SPSS 23.0 for windows program. The results in this study indicate a very significant relationship between family social support and self-acceptance of Islamic boarding school students, indicated by a value of r = 0.673 p = 0.000 (p <0.01) the higher the family social support, the higher the self-acceptance of Islamic boarding school students.